Innovation and Intellectual Property in Zimbabwe: A Discussion - MABHODYERA, GAMALIEL; MACHAKA, JUDITH; CHIPETIWA, MARKNOUGHLER (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2024)
Modern day financial corruption, poverty, ineffective social security, coupled with rapid increase in globalisation has, for years, left a detrimental dent on innovation and development. Generally, education, knowledge and skill are key to the development of country‘s economies. The article argues that the snail pace innovation in Zimbabwe has been a result of poor education policies which centred more on research than industrialisation. The article, therefore, discusses the evolution of the education system in Zimbabwe towards production and its relation to the law of intellectual property (IP). The goal of innovation is to have local, national and global impacts which can correspond to the stability of the economy. The study demonstrated how the Ministry of Higher and Tertiary Education, Innovation, Science and Technology Development has been instrumental towards the uplifting of the education system. Furthermore, the Education 5.0 curriculum has been viewed as an important aspect towards problem solving, whereby tertiary institutions play an important role in a common journey of development. The second part of the article unmasks the extent to which the existence of IP as a pro field of innovation has been lagging behind due to the disrespect and ill consideration of IP rights. The article establishes the relationship between creativity and innovation, which when new ideas are proposed, new skills are implemented based on thorough research. What remains as a catalyst is the rate at which such an idea can be successfully implemented. Therefore, on the final part, having outlined the existing dilemmas and problems, the article provides; lessons and recommendations on how the two (innovation and creativity) integral aspects of development can be used wisely for the betterment of social and economic fields.